Great Adventures and Explorations. From the Earliest Times to the Present, as told by the Explorers Themselves. - Stefansson, Vilhjamur (The Dial Press, 1947)
Presenta una serie de relatos que hacen referencia a las grandes exploraciones y descubrimientos del mundo actual.